Sobre o emprego de tijolos e blocos de vedação com função estrutural em edificações de pequeno porte - Noboa Filho, Salvador (2007)
The small and medium size, ground or one floor constructions in the inner São Paulo state, specially the residential ones, are predominantly build with massive ceramic brick or structural function closure blocks without structural concrete (beam or columns). This is known as resistant masonry. This building way is not standardized in Brazil. It shows one similarity to structural masonry: the resistant masonry concept, or the masonry besides the closure function, is also the main structural element. Nevertheless, it does not attend to others construction process characteristics, like dimension and detail process (project), material and execution technological control. In this kind of work, the masonry resistance specification is empirical determined, largely supported by the local workers professional experience and, eventually, by an engineer, documented solely by a city hall standard This study is focused on the resistant masonry building. The usual techniques are discussed ant the main criterion witch may be applied to the wall s dimension according to the Brazilian, British and European community rules. Using representative examples, find out calculations requested by walls are estimated according to different hypothesis of vertical loads distribution, the resistant capacity according to the dimension criterion applied by the Brazilian (adapted if necessary), British and European rules are determined; this values are then compared with the resistance of prism of varied material kinds used in this constructions (brick and blocks) obtained in tests. Based on these results, the structural viability is assessed. One of the many conclusions is the potential suitable use of the massive brick and the relevance of the international standard adoption to the dimension process, to fulfill the small building Brazilian structural masonry standard omission.